ПОЛІТИЧНА БОРОТЬБА В ПІВДЕННОУКРАЇНСЬКОМУ РЕГІОНІ ПІД ЧАС ВИБОРІВ ДО ВСЕРОСІЙСЬКИХ УСТАНОВЧИХ ЗБОРІВ (1917 р.) (Zaporizhzhia Historical Review, 2021)
The article considers the specificity of party and political struggle during the elections to the All-Russian Constituent Assembly in 1917. The peculiarities of organizing the electoral process are discovered, the data about the results of election campaign are cited. The author comes to a conclusion that a support given by local inhabitants to Ukrainian social parties increased substantively.